Acute Kidney Injury Interacts With Coma, Acidosis, and Impaired Perfusion to Significantly Increase Risk of Death in Children With Severe Malaria . (29th March 2022) - Namazzi, Ruth; Opoka, Robert; Datta, Dibyadyuti; Bangirana, Paul; Batte, Anthony; Berrens, Zachary; Goings, Michael J; Schwaderer, Andrew L; Conroy, Andrea L; John, Chandy C
Abstract: Background: Mortality in severe malaria remains high in children treated with intravenous artesunate. Acute kidney injury (AKI) is a common complication of severe malaria, but the interactions between AKI and other complications on the risk of mortality in severe malaria are not well characterized. Methods: Between 2014 and 2017, 600 children aged 6–48 months to 4 years hospitalized with severe malaria were enrolled in a prospective clinical cohort study evaluating clinical predictors of mortality in children with severe malaria. Results: The mean age of children in this cohort was 2.1 years (standard deviation, 0.9 years) and 338 children (56.3%) were male. Mortality was 7.3%, and 52.3% of deaths occurred within 12 hours of admission. Coma, acidosis, impaired perfusion, AKI, elevated blood urea nitrogen (BUN), and hyperkalemia were associated with increased mortality (all P < .001). AKI interacted with each risk factor to increase mortality ( P < .001 for interaction). Children with clinical indications for dialysis (14.4% of all children) had an increased risk of death compared with those with no indications for dialysis (odds ratio, 6.56; 95% confidence interval, 3.41-12.59). Conclusions: AKI interacts with coma, acidosis, or impaired perfusion to significantly increase the risk of death in severe malaria. Among children with AKI, those who have hyperkalemia or elevated BUN have a higher risk of death. A better understanding of the causes of these complications of severe malaria, and development and implementation of measures to prevent and treat them, such as dialysis, are needed to reduce mortality in severe malaria. Abstract : In children with severe malaria, concurrent acute kidney injury (AKI) significantly increases the mortality associated with coma, acidosis, or impaired perfusion. Interventions that address AKI complications, such as peritoneal dialysis, have the potential to decrease mortality in severe malaria.